Disparate Impacts of Broadband on Women and Minorities: The Case of Broadband in the U.S. - Mark A. Jamison; Peter Wang (International Telecommunications Society (ITS), 2023)
We examine broadband's impacts on entrepreneurship, income, and employment in general and separately by gender and for whites versus minorities in the U.S. for 2000 - 2019. Using Current Population Surveys and matching, we find that broadband access significantly impacted the decision to be self-employed until at least 2012. Broadband access also reduced unemployment and increased earnings. It generally benefitted women and minorities more than men and whites, but not always. Broadband was particularly effective for minority males and females during the years up to and immediately following the Great Recession. These findings are consistent with the idea that broadband may dampen gender and racial bias. The effects of broadband generally diminish as adoption increases, consistent with the belief that late adopters benefit less than early adopters.
Keywords: L86; L26; J71; L53; 330; broadband; entrepreneurship; discrimination; income; unemployment